2021
DOI: 10.3389/fdgth.2021.594971
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of Artificial Intelligence Implementation in Healthcare

Abstract: Background: Artificial Intelligence (AI) in healthcare has demonstrated high efficiency in academic research, while only few, and predominantly small, real-world AI applications exist in the preventive, diagnostic and therapeutic contexts. Our identification and analysis of success factors for the implementation of AI aims to close the gap between recent years' significant academic AI advancements and the comparably low level of practical application in healthcare.Methods: A literature and real life cases anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The last objective (4) consists of offering recommendations to the healthcare professionals to minimize the dilemmas and consider the implementation of AI, quite comprehensively. Previous research conducted by Wolff (2021) suggested 3 key success factors of AI in healthcare sector. The first factor recommends the setting of a risk adjusted policy frame that clarifies the limits of actions in term of precautions, permissions, accountability, liability and culpability.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last objective (4) consists of offering recommendations to the healthcare professionals to minimize the dilemmas and consider the implementation of AI, quite comprehensively. Previous research conducted by Wolff (2021) suggested 3 key success factors of AI in healthcare sector. The first factor recommends the setting of a risk adjusted policy frame that clarifies the limits of actions in term of precautions, permissions, accountability, liability and culpability.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The second success criteria suggest maintaining a centralized technology architecture that allows for practical and lawful metadata. Finally, Wolff (2021) highlights the necessity of having key performance indicators (KPI) that measure the medical and economic impact of AI in healthcare. Building on that, we suggest 4 key success factors of AI in healthcare sector that could potentially reduce the impact of the observed ethical dilemmas.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Independent Consultant in Computational Intelligence, Amsterdam, The Netherlands Table 1 summarizes the outcomes of the largest, most recent articles on postoperative complication prediction with ML in major abdominal surgery. The shift to clinical implementation will depend on five main improvement categories: technology, policy, medical and economic impact, transparency, and reporting [4,16,17].…”
Section: Barriers and Solutionsmentioning
confidence: 99%
“…Following factors need to be considered in implementation of AI in healthcare settings: Policy setting which involves a risk adjust policy, technological implementation, and medical and economic impact quantification. [48] There are several challenges that stand in the way of wider adoption of AI. These include: Workflow integration, enhanced explainability and interpretability, workforce education on how to use AI, appropriate regulatory mechanisms, problem identification and focusing on intervention drive AI, understanding the potential impact of AI on clinician and patient relationship and data quality, access, and sharing and compliance with privacy.…”
Section: Future Of Ai In Drmentioning
confidence: 99%